1989
DOI: 10.2134/agronj1989.00021962008100040017x
|View full text |Cite
|
Sign up to set email alerts
|

Dicamba Injury to Soybean

Abstract: Dicamba (3,6‐dichloro‐2‐methoxybenzoic acid) effectively controls many dicotyledonous weeds, but nontarget species such as soybean [Glycine max (L.) Merrill) are susceptible to spray or vapor drift. Field studies were conducted on a Canfield silt loam (fineloamy, mixed, mesic Aquic Fragiudalf) soil to determine the response of ‘Elf’ and ‘Williams’ soybean to dicamba over a wide range of applied rates, and to evaluate the use of dicamba injury symptoms to predict yield reductions. Soybean yield in response to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
151
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(163 citation statements)
references
References 3 publications
10
151
1
1
Order By: Relevance
“…Second, approximate stages of peanut growth were R1 (beginning bloom), R3 (beginning pod) and R6 (full seed) at 30, 60, and 90 DAP, respectively. In soybean, dicamba caused greater yield reductions when exposure occurred at bloom (Auch and Arnold, 1978;Wax et al, 1969;Weidenhamer et al, 1989). Similar results have also been observed in cotton (Hamilton and Arle 1979).…”
Section: Resultsmentioning
confidence: 64%
“…Second, approximate stages of peanut growth were R1 (beginning bloom), R3 (beginning pod) and R6 (full seed) at 30, 60, and 90 DAP, respectively. In soybean, dicamba caused greater yield reductions when exposure occurred at bloom (Auch and Arnold, 1978;Wax et al, 1969;Weidenhamer et al, 1989). Similar results have also been observed in cotton (Hamilton and Arle 1979).…”
Section: Resultsmentioning
confidence: 64%
“…1, 3, and 4; Table 3). The available literature suggests that small yield losses could be expected from a 0.56 g acid equivalent/ha exposure to susceptible soybean varieties [7,19,[35][36][37][38]. Because our experimental design does not include assessment of particle drift or additional routes of exposure including residual herbicide in spray equipment [5] or atmospheric deposition [34], total nontarget exposures to crops and wild plants could be substantially greater than our predictions for vapor drift.…”
Section: Dose-distance Relationshipsmentioning
confidence: 99%
“…More research is also needed to fully understand the response of nontarget plants to these low-dose exposures. The available literature suggests that small yield losses could be expected from a 0.56 g acid equivalent/ha exposure to susceptible soybean varieties [7,19,[35][36][37][38]. However, data from the U.S. EPA vegetative vigor tests associated with the registration of dicamba products also indicate that 0.56 g acid equivalent/ha is well below the 25% effective concentration for biomass (or the dicamba dose affecting a 25% reduction in biomass) for several crops in the seedling stage, including soybean, tomato, canola, and cucumber, indicating little risk [39,40].…”
Section: Dose-distance Relationshipsmentioning
confidence: 99%
“…Soybean, cotton (Gossypium hirsutum L.), and grain sorghum (Sorghum bicolor) are among the crop species most susceptible to synthetic auxin herbicides, such as dicamba, 2,4-D, and florpyrauxifen-benzyl. Previous research has reported numerous consequences of dicamba drift onto non-dicambaresistant soybean, such as reduced growth, fewer seeds per pod, lower seed quality, maturity delays, and pod malformation [16][17][18][19][20]. Symptomology can vary from chlorosis of the terminal buds, cupping or crinkling of canopy leaves, and leaf or stem epinasty.…”
Section: Introductionmentioning
confidence: 99%